IbM: IMPLENTASI SISTEM IRIGASI SUMUR DALAM PADA KELOMPOK TANI PADI ORGANIK UNTUK MENINGKATKAN PRODUKSI PADI ORGANIK [IbM: IMPLEMENTATION OF AN IRRIGATION WELL SYSTEM FOR THE ORGANIC RICE FARMER GROUP TO INCREASE THE PRODUCTION OF ORGANIC RICE] - Sumani Sumani; Joko Winarno; Supriyadi Supriyadi (Universitas Pelita Harapan, 2017)
The organic farming community Al Barokah was formed in the village of Ketapang, sub-district of Susukan, district of Semarang in 2004, which includes the farmer group Al Barokah 3 and the farmer group Walisongo. The wish to cultivate organic rice has arisen in 2002, and was followed-up by studies for more information, know-how and skills. The area of land that is cultivated organically increases steadily each year, and is currently almost 300 ha. In 2015, through the accompaniment of LPPM UNS, an organic certificate from organic certification institution was obtained. One of the important problems faced by the organic farming community Al Barokah is the availability of water for irrigation, especially in dry season. Therefore, there is a need for a science-technology (Iptek) program for the community: Implementation of an irrigation well system for the organic rice farmer group to increase the production of organic rice. The project is conducted from June to October2017. Group participative method is used, because active participation from the community in every step of the program is required by supporting the resources of the farmer group.